The Matter of Mimesis Studies of Mimesis and Materials in Nature, Art and Science - Bol, Marjolijn; Spary, E. C. (Brill, 2023)
Mimesis or imitation comes in many forms, from animal and plant mimicry to artistic copies 'from life'. This book offers eighteen essays addressing mimesis from diverse perspectives. From the recreation of galaxies to Iron Age torcs, from counterfeit dragons to modern waxworks, each chapter explores facets of material mimesis from prehistory to the present day. The Matter of Mimesis invites readers to compare practices of imitating, faking, and synthesising materials and objects in nature, art and science, raising questions about skills, techniques and politics of making that transcend historical and disciplinary boundaries and inform both our past and future worlds.